Substantive Inequality in Article 116 (b) and (c) of the Kompilasi Hukum Islam: A Rawlsian Analysis of Divorce Law Reform - Muhammad Danias Salsabila; Abd. Rouf; Syaikhoni (KALOSARA: Family Law Review, 2026)
The regulation of divorce grounds in Article 116 of the Kompilasi Hukum Islam (KHI), particularly letters (b) and (c), reveals a temporal disparity that affects parties’ access to justice. Although widely discussed in normative and judicial contexts, studies applying a Rawlsian framework especially the difference principle remain limited. This study examines whether these temporal differences constitute substantive inequality and whether they are normatively justifiable. Using normative legal (doctrinal) research with statutory and conceptual approaches, the study operationalizes John Rawls’ theory of justice as an evaluative framework to assess the distribution of legal protection for the least advantaged. The findings show that the disparity between Article 116 (b) and (c) reflects substantive inequality, as it applies inconsistent time- and status-based parameters to situations that are essentially similar, namely the failure to fulfill marital obligations. Such inequality cannot be fully justified under the difference principle, as it may prolong or generalize the harm suffered by disadvantaged parties. Accordingly, this study argues for a shift from a formally time-based approach toward one based on substantive impact, to ensure that divorce law is more responsive in protecting vulnerable individuals. Keywords: Article 116; Divorce; John Rawls’ Theory of Justice; Kompilasi Hukum Islam.